ASSESSMENT OF PRINCIPALS’ USE OF INFORMATION AND COMMUNICATIONS TECHNOLOGY FOR EFFECTIVE MANAGEMENT OF SECONDARY SCHOOLS IN ANAMBRA STATE - OBINEME, PATIENCE OBIAGELI; AGUBA, CHINEDU .R. (Int’l Journal of Education Research and Scientific Development, 2025)
The main purpose of the study was to assess principal utilization of information and communication technology for effective management of secondary schools in Anambra State. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. The descriptive survey research design was adopted for the study. The population comprised 5,136 individuals, including 265 principals and 4,871 teachers across 265 secondary schools in the state’s six education zones. A sample of 1,027 principals and teachers was selected using multi-stage, proportionate random sampling, with 20% of the population chosen. Data collection was carried out using a self-constructed questionnaire which was validated by experts. The reliability of the instrument was ascertained through a pilot test in Enugu State. Test on the data collected using Cronbach Alpha yielded coefficient of 0.73 and 0.82 for cluster 1 and 2 respectively with a grand coefficient of 0.78. Mean, standard deviation and t-test was used to analyze data for the study. The finding of the study revealed that principals utilize ICT in planning process for effective management of secondary schools in Anambra State to a low extent. Similarly, principals’ utilization of ICT in record keeping process for effective management of secondary schools in Anambra State was to a low extent. Principals and teachers did not differ in their opinions on the extent of principals’ utilization of ICT for effective management of secondary schools in Anambra State. Based on the findings of the study, the researcher recommended among others that the state government and relevant educational authorities should organise regular capacity-building workshops and training programmes for principals.